Bell's palsy. Issue 12 (December 2021) - Cull, Frith; Coleman, Holli
Bell's palsy is the term given to an idiopathic lower motor neurone facial nerve paresis or paralysis. It is of rapid onset, almost always unilateral, and may be associated with facial or retro-auricular pain or otalgia. It is the most common diagnosis associated with facial nerve palsy; a GP will see a case approximately every 2 years in practice in the United Kingdom. Early diagnosis and steroid treatment increase the likelihood of full recovery, whereas ocular complications can be prevented by lubricants and lid taping. Over 70% of patients recover within a year. Options to improve facial appearance and function, in those who do not experience a complete recovery, include surgery.